Ganoderma boninense Penyebab Penyakit Busuk Batang Atas Kelapa Sawit - Agus Susanto; Agus Eko Prasetyo; Hari Priwiratama; Sri Wening; Surianto Surianto (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2013)
Basal stem rot disease (BSR) caused by Ganoderma boninense is the major pathogen of oil palm in Indonesia and Malaysia. Sometimes in the same location, especially in the peatland, upper stem rot (USR) disease is also found. This research was carried out to identify the pathogen of upper stem rot by molecular approach. Fruiting bodies of fungus were collected from 3 plants with upper stem rot symptoms and 2 plants with basal stem rot symptoms from Labuhan Batu North Sumatra and Kampar Riau. Results showed that all of the fruiting body samples taken from plants with upper stem rot and basal stem rot symptoms were G. boninense.